Do male 100-km ultra-marathoners overdrink? - Knechtle, B.; Knechtle, P.; Rosemann, T. (International Journal of Sports Physiology and Performance, 2011)
Purpose: Fluid overload is considered a main risk factor for exercise-associated hyponatremia (EAH). The aim of this study was to investigate the incidence of EAH in ultra-runners at the 100 km ultra-run in Biel, Switzerland. Methods: Pre- and postrace, body mass, urinary specific gravity, hemoglobin, hematocrit, plasma [Na+], and plasma volume were determined. Results: Of the 145 finishers, seven runners (4.8%) developed asymptomatic EAH. While running, the athletes consumed a total of (median and interquartile ranges) 6.9 (5.1-8.8) L over the 100 km distance, equal to 0.58 (0.41-0.79) L/h. Fluid intake correlated negatively and significantly with race time (r = -.50, P < .0001). Body mass decreased, plasma [Na+] remained unchanged, hematocrit and hemoglobin decreased, and urinary specific gravity increased. Plasma volume increased by 4.6 (-2.3 to 12.8) %. Change in body mass correlated with both postrace plasma [Na+] and d plasma [Na+]. Postrace plasma [Na+] correlated to d plasma [Na+]. Fluid intake was associated neither with postrace plasma [Na+] nor with d plasma [Na+]. Fluid intake was related to body mass (r = .21, P = .012), but not to postrace body mass. Fluid intake showed no correlation to d plasma volume. Change in plasma volume was associated with postrace [Na+]. Conclusions: Incidences of EAH in 100 km ultra-marathoners were lower compared with reports on marathoners. Body mass decreased, plasma volume increased, and plasma [Na+] was maintained. Since fluid intake was related neither to d plasma volume nor to d plasma [Na+], we assume that factors other than fluid intake maintained body fluid homeostasis.